Perceived controllability of a SARS-CoV-2 infection: an investigation of intersectional differences - Till Neugebauer; Diana Wahidie; Fabian Erdsiek; Yüce Yilmaz-Aslan; Patrick Brzoska (BMC, 2022)
Abstract Background The perceived ability to influence an infection with SARS-CoV-2 has an impact on compliance with protective measures. Factors influencing perceived controllability are not yet fully known. The aim of this study was to identify intersectional differences in perceived controllability. Insights into these intersectional differences could help to develop user-centered strategies to improve the acceptance of protective measures. Methods Data from the seventh wave of the German Ageing Survey (DEAS) was used to investigate differences in the population regarding the perceived controllability. The role of socio-demographic and socio-economic predictors was investigated using multivariable linear regression modeling. Intersectional differences were examined using interaction terms. Results Information on 4,823 respondents aged 46 to 100 years were available, of which 50.9% were female. Migration status (yes vs. no: β = -0.27; 95%-CI = -0.48,-0.06), education level (high vs. low: β = 0.31; 95%-CI: 0.08, 0.55) and employment status (retired vs. employed: β = 0.33; 95%-CI: 0.19, 0.48) were found to be significantly influencing perceived controllability. Interaction effects were found with respect to sex and migration status, with migrant women rating their perceived controllability lower than non-migrant women (β = -0.51; 95%-CI = -0.80, -0.21), while no differences were evident between migrant and non-migrant men (β = -0.02; 95%-CI = -0.32, 0.28). Further intersectional differences were not observed. Conclusions The results show that intersectional differences in perceived controllability occur especially between migrant and non-migrant women. Possible causes may lie in language barriers, which in connection with lower health literacy may affect perceived controllability. Dedicated efforts to improve controllability among older adults, those with lower educational attainment and migrant women are warranted.